2008
DOI: 10.1359/jbmr.080607
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Metabolites and Calcium Absorption in Severe Vitamin D Deficiency

Abstract: Contrary to frequent claims, vitamin D insufficiency does not generally cause malabsorption of calcium because serum 1,25(OH) 2 D, which is the major determinant of calcium absorption, is maintained by secondary hyperparathyroidism. Nevertheless, because malabsorption of calcium has been described in osteomalacia, there must be a 25(OH)D level below which the serum 1,25(OH) 2 D can no longer be sustained, although it has never been defined. This paper seeks to define it. We examined the records of 3661 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
4
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(139 citation statements)
references
References 25 publications
2
130
4
3
Order By: Relevance
“…The 7 ng/mL rise in serum 25(OH)D at a vitamin D dose of 400 IU/d of vitamin D 3 is slightly greater than the estimated approximately 1 ng/mL (2.5 nmol/L) rise for every 100 IU/d (2.5 mg) of vitamin D (1) but consistent with other studies where baseline serum 25(OH)D was low and supplemental intake was 400 IU/d. (24,25) In contrast to other vitamin D intervention studies in which PTH is suppressed and 1,25(OH) 2 D 3 levels do not change following vitamin D therapy, (3,22,26) our study showed that ALN þ D increased both 1,25(OH) 2 D 3 and PTH levels. Increases in both 1,25(OH) 2 D 3 and PTH have been reported by others following onset of alendronate therapy.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…The 7 ng/mL rise in serum 25(OH)D at a vitamin D dose of 400 IU/d of vitamin D 3 is slightly greater than the estimated approximately 1 ng/mL (2.5 nmol/L) rise for every 100 IU/d (2.5 mg) of vitamin D (1) but consistent with other studies where baseline serum 25(OH)D was low and supplemental intake was 400 IU/d. (24,25) In contrast to other vitamin D intervention studies in which PTH is suppressed and 1,25(OH) 2 D 3 levels do not change following vitamin D therapy, (3,22,26) our study showed that ALN þ D increased both 1,25(OH) 2 D 3 and PTH levels. Increases in both 1,25(OH) 2 D 3 and PTH have been reported by others following onset of alendronate therapy.…”
Section: Discussioncontrasting
confidence: 78%
“…(28) Researchers found no significant increase in calcium absorption from baseline to 2 years among 39 postmenopausal women who received 1000 IU of vitamin D daily along with 1200 mg of calcium. (29) Finally, in a randomized, double-blind, controlled pilot trial conducted simultaneously with this study, with identical recruitment criteria to this protocol, 12 postmenopausal women (age 57 AE 6 years, BMI of 28.6 AE 6.9 kg/m 2 ) were assigned to 1200 mg of calcium daily and either 5 weeks of 400 IU/d vitamin D 3 or placebo (n ¼ 6/ group). (26) Mean baseline serum 25(OH)D was 20.8 AE 6.3 ng/mL, and the change in 25(OH)D differed between the vitamin D group (þ5.5 AE 3.9 ng/mL) and the placebo group (À1.2 AE 3.8 ng/ mL, p ¼ .013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational data have revealed that 25(OH)D levels predict the decline in bone mineralization and physical performance when 25(OH)D falls below 8 and 20 ng/mL (20 and 50 nmol/L), respectively 8, 56. Although the underlying mechanisms remain to be elucidated, vitamin D may represent a pathway by which bone and muscle may work together, enabling cross‐talk between these tissues ( Figure  3).…”
Section: Vitamin D Physiologymentioning
confidence: 99%
“…Differences in these recommended target ranges are attributed to controversies regarding 25(OH)D intestinal calcium absorption, maximal suppression of PTH, or optimal levels to prevent a clinical end‐point such as fracture or death:

Adequate intestinal calcium absorption . The adequate 25(OH)D levels to guarantee sufficient substrate for its conversion to 1,25(OH) 2 D and ensure optimal calcium absorption has been estimated to be >4.4 ng/mL (11 nmol/L) 158. However, this definition may be unsuitable for CKD patients, in whom calcium absorption and 1,25(OH) 2 D production are impaired 159

…”
Section: Controversies In the Definition Of Vitamin D Insufficiency Imentioning
confidence: 99%